PELATIHAN PIJAT OKSITOSIN PADA IBU MENYUSUI MELALUI KELAS ASI DI PMB MIMIK SUWARMININGSIH Amd.Keb KECAMATAN MUMBULSARI KABUPATEN JEMBER - Tyas, Trisna Pangestuning; Perbawati, Dinar; Astiti, Arien Daning; Margaretha, Vitha (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Oxytocin massage is done by massaging the back area along both sides of the spine, so it is hoped that by doing this spinal massage, the mother will feel relaxed and the fatigue after giving birth will soon disappear. If the mother is relaxed and not tired, it can help release oxytocin. Massage on the spine, will stimulate neurotransmitters in the medulla oblongata with directly sending messages to the hypothalamus in the posterior pituitary to release oxytocin, it causing the breasts to release milk. This Community Service activity is expected to be able to provide both theoretical knowledge and skills to Breastfeeding Mothers at Mimik Suwarminingsih, Amd.Keb Midwifery independent service and help mothers who have difficulty breastfeeding. This community service activity uses promotion, support and empowerment methods. The Breastfeeding class provides complete information about oxytocin message to help increase milk production